ANALYSIS CORRELATION CAPITAL STRUCTURE, POLICY DIVIDENDS, GOOD CORPORATE GOVERNANCE, OPPORTUNITIES GROWTH AND PROFITABILITY ON FIRM VALUE IN MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE 2019-2024 - Angela Ayu Kusumaning Ratri; Astri Wening Perwitasari; Aditya Narendra Wardhana; Mirza Dwinanda Ilmawan (RADJA PUBLIKA, 2025)
This research study is about the correlation between capital structure, dividend policies, good corporate governance (GCG), opportunities for growth, and profitability with the firm value of manufacturing companies that are listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024. By using the purposive sampling method, we obtained a sample of 120 companies with a total of 720 observations (firm-year). Firm value is measured using Price to Book Value (PBV). At the same time, variables include the Debt-to-Equity Ratio (DER), Dividend Payout Ratio (DPR), institutional ownership, independent board of commissioners, independent audit committee, Market to Book Value of Equity (MBVE), Return on Equity (ROE), and company size (Ln Asset). Because data distribution is not normal, the research uses the Spearman correlation test. The results indicate that DPR, MBVE, ROE, and the proportion of commissioner independence have a positive and significant connection with the market company in the upcoming year. On the other hand, DER, ownership institutions, the audit committee, and company size do positively impact market value. These findings confirm that profitability, policy dividends, growth opportunities, and governance effectiveness through the role of the independent commissioner all contribute significantly to increasing firm value. Managerial implications indicate that the company needs to prioritize improvement strategies for profitability, maintain consistent dividend policies, strengthen governance quality, and utilize growth opportunities strategically to enhance market and investor confidence.